PEMBERDAYAAN MASYARAKAT DALAM PROSES PEMBELAJARAN MENGHADAPI UJIAN NASIONAL : Studi Situs SMP Negeri 1 Ceper Klaten - Subandi , Subandi (2011)
This research general purpose is description wish to condition of involvement reality of public in education, while purpose of special description of enableness wish to of enableness public in process of study faces national test as school partner and government. This research approach is qualitative research, is research about data collected and expressed in the form of words compiled in sentence. Research approach applies fenomenology. Research subject is committee chief, headmaster, and teacher, and parent. Data collecting method applies in-depth interview, observation, and documentation. Analysis data analytical technique interactive. authenticity of data applies trianggulation technique. Result of research that is : Enableness of public in process of study faces national test can be done in the form of giving idea inputs, proposal about school program as according to requirement of public, gives contribution of fund or defrayal in the effort supporting school program operational. The role of school in process of study faces national test is executed with effective study activity, construction and tuition of extracurricular activity like boy scout, athletics, les or addition of hour (clock evening learning, performs a communication and forwarding of information of school program through school committee plenary meeting, etcetera. School characteristic and public in process of study faces national test in State Junior High School 1 Ceper Klaten by the way of increasing service to public especially student parent, cooperates in compiling activity plan, execution, and reporting which accountable and open. Despitefully, existence of feedback in increasing quality of education which in the form of activity of communications and information periodical about various activities executed by school especially study process in facing national test passed les